Chitooligosaccharides production from shrimp chaff in chitosanase cell surface display system. (1st February 2022) - Chen, Yanli; Ling, Zhenmin; Mamtimin, Tursunay; Khan, Aman; Peng, Liang; Yang, Jinfeng; Ali, Gohar; Zhou, Tuoyu; Zhang, Qing; Zhang, Jing; Li, Xiangkai
Abstract: Chitin refers to a natural biopolymer, which is economically significant to next-generation biorefineries. In this study, a novel high-yield method with cell surface-display chitosanase (CHI-1) was built to produce chitooligosaccharides (COS) from shrimp chaff through the co-fermentation in the presence of Bacillus subtilis and Acetobacter sp. Under the optimized co-fermentation conditions (5 g/L yeast extracts, 10 g/L KH2 PO4, 6% ethanol, 50 g/L glucose), the final deproteinization (DP) and demineralization (DM) efficiency and the chitin yield were achieved as 94, 92 and 18%, respectively. The engineered E. coli BL21-pET23b(+)-NICHI maintained 81% of the initial enzyme activity after 40 days at room temperature. The crude CHI-1 was inactivated after one-day interacting with prepared chitosan. Moreover, E. coli BL21-pET23b(+)-NICHI still maintained excellent hydrolysis ability in 7 days, and the COS yield reached 41%. Accordingly, the proposed method exhibited excellent stability and a high hydrolysis efficiency to produce COS with whole engineered cells. Graphical abstract: Unlabelled Image